Erstaufnahme II - Ben-Yakov, Pablo; Eberhardt, Marc (Germany, 2016)
In 2014 the former barracks of Meßstetten will provide an accommodation for about 1000 refugees – Baden-Württemberg’s second reception center for refugees. The village counts only about 5000 inhabitants and the proximity to Southern Germany’s only military training ground results in constant reverberations of heavy artillery. While the facility’s staff is still getting used to their new tasks, the increasing number of refugees becomes what is known to be the „refugee crisis“.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films